Analysis of the Strategy of Surowiti Village in Increasing Village Budget Contribution - Jasmine, Aulia Bilqis; Akbar, Raffi Rizky; Shafiqah, Alvira Nindya; Rahayu, Settriya; Sonhaji, Haidar Adriel Zavier (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study analyzes the development strategies implemented by Surowiti Village ini increasing its contribution to the village budget, especially through the optimization of local potential. Using a qualitative descriptive approach, data were collected through interviews, observation and documentation involving key village stakeholders. The findings reveal that religious tourism, particularly the spiritual site of Sunan Kalijogo’s hermitage, serves as the main driver in generating Villang Original Income (PADes). The involvement of community-based institutions, such as BUMDes, strengthens the institutional capacity and management of village resources. Moreover, participatory planning and collaboration with external parties such as local governments and the private sector have proven effective in supporting strategy implementation. However, challenges remain, including limited human resources, infrastructure and managerial skills. The study concludes that inclusive and locally-driven strategies are key to enhancing fiscal independence and promoting sustainable village development.